No alhures do sentido: reflexões sobre a tradução de Lacan no Brasil a partir de duas experiências tradutórias do Seminário 11 - Martins, Lia Bezerra (2020)
The work of the French psychoanalyst Jacques Lacan, who takes the Freudian discovery as a point of departure and arrival, is constructed as a discourse of strongly marked style, full of neologisms, polyglossia, intertextuality and a mixture of registers, in addition to extreme syntactic manipulation – formal characteristics which, being inseparable from the content, impose on the translation the need for a particular treatment. The work presented here aims to explain, on the basis of a bibliographical research, the ethical, aesthetical and epistemic implications of the Lacanian style in the transmission of psychoanalysis, in order to discuss its effects on translation, examining, by means of a comparative case study, the strategies adopted by M.D. Magno and Claudia Berliner in the translation of the first five lessons of Seminar 11 into Brazilian Portuguese. The analysis focuses primarily on the subjective position assumed by each translator in relation to the otherness of language, particularly regarding the colonial implications of translating from a central language to a peripheral one. In such manner, the study examines which factors determine the ethical and political conception of each translation, and how the strategies adopted impact on the texture and readability of Lacan’s text in Brazilian Portuguese.